Gizi Seimbang untuk Pencegahan Anemia - Purwati Purwati (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2020)
Anemia in pregnancy is a problem due to a lack of red blood cells during pregnancy. Partner problems are 1) pregnant women do not attend the class of pregnant women, 2) the high number of pregnant women with anemia is 5 out of 15 pregnant women and KEK 1 person. This IbM activity is a collaboration between the D3 Midwifery Study Program, especially in the Community sector with Midwives in Karangtengah village, Kembarang sub-district, Banyumas district. This activity is carried out through a pregnant woman class as a forum for pregnant women to learn about the physiology and discomfort of pregnancy and how to overcome them. The results obtained are in accordance with the initial planning, namely: the reactivation of the class of pregnant women in PKD Karangtengah village, increased knowledge of pregnant women about balanced nutrition in pregnancy, the existence of health education media about balanced nutrition in the PKD class of pregnant women in Karangtengah village.